2022
DOI: 10.3390/joitmc8010051
|View full text |Cite
|
Sign up to set email alerts
|

Maturity of Industry 4.0: A Systematic Literature Review of Assessment Campaigns

Abstract: The Industry 4.0 paradigm represents the fourth industrial revolution, embodied by the marriage between information and communication technologies and manufacturing. Assessment campaigns are conducted to examine the status of deployment of that paradigm, mostly through self-assessment questionnaires. Each campaign is typically limited in scope, involving just a group of companies located in a few countries at most. Such limitation does not allow an overall view of Industry 4.0’s diffusion. In this paper, we of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Several studies have focused on establishing models to analyze and assess the maturity of industrial organizations with respect to Industry 4.0 (Elibal and Özceylan, 2021; Flamini and Naldi, 2022). In these survey studies, the focus is more on the readiness of industrial organizations and service industries than on the readiness of HEIs.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies have focused on establishing models to analyze and assess the maturity of industrial organizations with respect to Industry 4.0 (Elibal and Özceylan, 2021; Flamini and Naldi, 2022). In these survey studies, the focus is more on the readiness of industrial organizations and service industries than on the readiness of HEIs.…”
Section: Related Workmentioning
confidence: 99%
“…A 2022 study conducted by Flamini & Naldi [9] performed a systematic literature review using Scopus and Web of science to identify and review all assessment campaigns published regarding Industry 4.0 across all industries. The paper reviewed 85 different models published between 2017 and 2021 and summarized the findings by identifying 11 assessments as "established models".…”
Section: Relevant Models From Literature -Stepmentioning
confidence: 99%
“…Since Flamini & Naldi [9] executed a thorough and systematic literature review for all models published in the last five years, performing a new bibliometric analysis is highly unlikely to yield different results. Thus, this study will use the 11 established models that [9] identified. The models are explained below.…”
Section: Relevant Models From Literature -Stepmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, numerous existing works focus on food security, factors affecting it [ 9 ], challenges and new strategies to endure the food demands, and sustainability of food security [ 9 , 10 ]. Industry 4.0 aims to revolutionize the industrial processes from design to products by integrating information and communication technologies (ICTs) such as IoT, industrial IoT (IIOT), robots, cloud computing, big data analytics, artificial intelligence (AI), and machine learning (ML) [ 11 ]. These ICTs have introduced significant benefits in various applications [ 12 ].…”
Section: Introductionmentioning
confidence: 99%